Building a travel risk management program : traveler safety and duty of care for any organization - Brossman, Charles (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Building a Travel Risk Management Program: Traveler Safety and Duty of Care for Any Organization helps business and security professionals effectively manage traveler risk by showing them how to build a complete travel risk program. While global corporate travel risks are increasing exponentially, many security and business managers are not well-versed in the rapidly changing global landscape of travel risk, nor do they fully realize the multitude of risks their companies face if they don't comply with their legal obligations-"duty of care"--For protecting their employees from foreseeable harm, which can cost a company in the form of extensive fines, productivity loss, business interruptions, stock price loss, litigation, and even potential bankruptcy. This book is the first to bridge the gap between the topics of travel management, security, and risk management. It serves as a reference point for working with other departments, including human resources and legal, paving the way for better internal cooperation for travel managers and security managers. In addition, it helps organizations craft a travel risk management program for their unique needs that incorporates the most important policies and procedures that help them comply with legal obligations